2020
DOI: 10.3390/pharmaceutics12090872
|View full text |Cite
|
Sign up to set email alerts
|

Low-Vacuum Filtration as an Alternative Extracellular Vesicle Concentration Method: A Comparison with Ultracentrifugation and Differential Centrifugation

Abstract: Recent years have brought great focus on the development of drug delivery systems based on extracellular vesicles (EVs). Considering the possible applications of EVs as drug carriers, the isolation process is a crucial step. To solve the problems involved in EV isolation, we developed and validated a new EV isolation method—low-vacuum filtration (LVF)—and compared it with two commonly applied procedures—differential centrifugation (DC) and ultracentrifugation (UC). EVs isolated from endothelial cell culture me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…It is the first report of the FTIR peak characteristics of EVs derived from plant material. The peaks in the present study are similar to those found in the EVs derived from mammals in other studies 50 54 .
Figure 3 ( a ) Primary (black line) and second derivative (blue line) FTIR spectra of biological compositions of EVs derived from Raphanus sativus L. var.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It is the first report of the FTIR peak characteristics of EVs derived from plant material. The peaks in the present study are similar to those found in the EVs derived from mammals in other studies 50 54 .
Figure 3 ( a ) Primary (black line) and second derivative (blue line) FTIR spectra of biological compositions of EVs derived from Raphanus sativus L. var.
…”
Section: Resultssupporting
confidence: 90%
“…FTIR was used to study the biological molecular compositions in EVs. In addition to proteins, lipids, and nucleic acids, carbohydrates were also detected in EVs derived from different sources e.g., serum 72 , milk 73 , and cell culture-conditioned media 50 . Carbohydrates were reported to be related to the EVs biogenesis 74 , cellular recognition, and uptake of EVs by recipient cells 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…200 mL) were collected and subjected to sequential centrifugation. Cells and cellular debris pelleted after centrifugations at 400× g (5 min, 4 °C) and 4500× g (20 min, 4 °C) were discarded, whereas supernatants were collected and concentrated by a low-vacuum filtration (LVF) procedure, as described in [ 24 ]. LVF was performed on the dialysis membrane (Repligen, Waltham, MA, USA, cat.…”
Section: Methodsmentioning
confidence: 99%
“…First, urine sample was centrifuged at 2000× g for 30 min at room temperature (RT), in order to remove bacteria, cell debris, and the majority of Tamm–Horsfall protein aggregates [ 35 ]. After the centrifugation step, the supernatant was collected and used for the Low-Vacuum Filtration (L-VF) method [ 36 ]. In this method, the urine sample was purified and concentrated using a 1000 kDa (MWCO) dialysis membrane, and a low vacuum (−0.3 Bar) was applied.…”
Section: Methodsmentioning
confidence: 99%